2005
DOI: 10.1063/1.1921408
|View full text |Cite
|
Sign up to set email alerts
|

Tracking frequency laser distance gauge

Abstract: Advanced astronomical missions with greatly enhanced resolution and physics missions of unprecedented accuracy will require laser distance gauges of substantially improved performance. We describe a laser gauge, based on Pound–Drever–Hall locking, in which the optical frequency is adjusted to maintain an interferometer’s null condition. This technique has been demonstrated with pm performance. Automatic fringe hopping allows it to track arbitrary distance changes. The instrument is intrinsically free of the nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It will be able to detect a violation of the EP with a fractional acceleration accuracy of 5 parts in 10 14 in a short (few days) experiment and 3 to 10 fold better in a longer experiment. The experiment makes use of optical distance measurement (by TFG laser gauge [82]) and will be advantageously sensitive to short-range forces with a characteristic length scale of λ < 10 km. SR-POEM, a POEM-based proposed room-temperature test of the WEP during a sub-orbital flight on a sounding rocket (thus, SR-POEM), was recently also presented [3].…”
mentioning
confidence: 99%
“…It will be able to detect a violation of the EP with a fractional acceleration accuracy of 5 parts in 10 14 in a short (few days) experiment and 3 to 10 fold better in a longer experiment. The experiment makes use of optical distance measurement (by TFG laser gauge [82]) and will be advantageously sensitive to short-range forces with a characteristic length scale of λ < 10 km. SR-POEM, a POEM-based proposed room-temperature test of the WEP during a sub-orbital flight on a sounding rocket (thus, SR-POEM), was recently also presented [3].…”
mentioning
confidence: 99%
“…It will be able to detect a violation of the EP with a fractional acceleration accuracy of 5 parts in 10 14 in a short (few days) experiment and 3 to 10 fold better in a longer experiment. The experiment makes use of optical distance measurement (by TFG laser gauge [24]) and will be advantageously sensitive to short-range forces with a characteristic length scale of λ < 10 km. SR-POEM, a POEM-based proposed room-temperature test of the WEP during a sub-orbital flight on a sounding rocket, was recently also presented [25].…”
mentioning
confidence: 99%
“…In Ref. 5 it is shown that, assuming that all ofthe available frequency shift range is used for measuring absolute distance, this is equivalent to a<::'i. (5) Yp For the current TFG, this requires c<1.6x 106,a two order ofmagnitude improvement.…”
Section: Precision Of Incremental and Absolute Distancementioning
confidence: 99%
“…5 In Section 3, we discuss the current implementation ofthe TFG and the results from tests ofthat version. Finally, in Section 4, we introduce a series of techniques that we plan to use as part of a more robust, capable, and potentially spaceworthy laser gauge that we are developing, which we call the "new TFG.…”
Section: Introductionmentioning
confidence: 99%